Philosophy 167: Class 13 - Part 13 - De Motu Corporum in Gyrum: Theorem 4, Problem 4, and Two Key Scholia. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Synopsis: Further mathematical analysis of De Motu.; Opening line: "Theorem for supposing that centripetal force be reciprocally proportional to the square root of the distance from the center."; Duration: 12:30 minutes.; Segment: Class 13, Part 13.